Anthropometric And Hypertensive Profile of Adolescents of Surat City: A Cross Sectional Study - Shailee Vyas; Mohua Moitra; Vipul P Chaudhari; S L Kantharia (Medsci Publications, 2014)
Introduction: Adolescence is a period of transition from childhood to adulthood. It is characterized by rapid physical, biological and hormonal changes resulting in to psychosocial, behavioural and sexual maturation between the ages of 10-19 years in an individual. Adolescence is often described as a phase of life that begins in biology and ends in society. Objective: To assess the profile of the adolescents of Surat city in relation to anthropometric and blood pressure parameters. Methods: A purposively selected sample of 450 college students & 150 out of college adolescents were studied. Those adolescents belonging in the age group of 17 to 19 years and willing to participate in the study were identified from one of the three prior identified colleges. Similarly adolescents not attending any college but who were literate and able to fill the self administered questionnaire were identified. These selected adolescents were studied between September 2010 and July 2011. Results: In both the college & out of college groups, 44% had a normal BMI. More of the colleges going adolescents were found to be overweight (8% as compared to 2.7% in out of college adolescents). Majority of the respondents were found to be having normal WHR with the college going group being on the higher side. Thus, it was observed that the proportion of hypertension observed was more in college students, especially those in the professional college and also more among boys as compared to girls. Conclusion: The proportion of hypertension was more in college students, especially those in the professional college and also more among boys as compared to girls.